The Impact of Extraintistinal amobiosis on TP53 Gene in Patients with Hepatocellular Carcinoma - Basheer. Abd. Nasralla (Journal of Global Pharma Technology, 2019)
In this study, 20 serum samples and 8 liver abscess biopsy specimens were taken from 20 hepatocellular carcinoma and E. histolytica infected patients. Laboratory findings of patients with liver abscess showed increased total white blood cell count (WBC), increased C-reactive protein, (AST), (ALT), alkaline phosphatase (ALP), gamma-glutamyl transpeptidase (GGT) and bilirubin. The result of PCR performed on liver abscess patients was positive for the DNA of E.histolytica infected patients and 8 biopsy liver abscess patients. To detect TP 53 gene in hepatocellular with liver abscess of all 8(100%), mutation occurred in sequences of TP53, and there were changes in several locations on the exons. Nucleotides changes were shown in TP53 gene Exon 147,152,160.203 and 235amplified from tumor liver cancer samples. The mutation occurred on nucleotides TCC, GGT, ACT, CGC and ATC of TP53 gene.Keywords: Extra intestinal amebiasis. TP53 gene, Hepatocellular carcinoma.